Engineering Supramolecular Polymer Conformation for Efficient Carbon Nanotube Sorting. Issue 26 (5th June 2020) - Gao, Theodore Z.; Sun, Zehao; Yan, Xuzhou; Wu, Hung‐Chin; Yan, Hongping; Bao, Zhenan
Abstract: Supramolecular polymer sorting is a promising approach to separating single‐walled carbon nanotubes (CNTs) by electronic type. Unlike conjugated polymers, they can be easily removed from the CNTs after sorting by breaking the supramolecular bonds, allowing for isolation of electronically pristine CNTs as well as facile recycling of the sorting polymer. However, little is understood about how supramolecular polymer properties affect CNT sorting. Herein, chain stoppers are used to engineer the conformation of a supramolecular sorting polymer, thereby elucidating the relationship between sorting efficacy and polymer conformation. Through NMR and UV–vis spectroscopy, small‐angle X‐ray scattering (SAXS), and thermodynamic modeling, it is shown that this supramolecular polymer exhibits ring–chain equilibrium, and that this equilibrium can be skewed toward chains by the addition of chain stoppers. Furthermore, by controlling the stopper–monomer ratio, the sorting yield can be doubled from 7% to 14% without compromising the semiconducting purity (>99%) or properties of sorted CNTs. Abstract : The addition of chain stoppers significantly improves carbon nanotube (CNT) sorting with an H‐bonding supramolecular polymer. In‐depth characterization reveals that this supramolecular polymer exhibits ring–chain equilibrium, and that stoppers skew the distribution toward chains, which can wrap CNTs more effectively. Careful selection of the stopper–monomer ratio results in doubling of the sorting yield without compromising the purity or properties of sorted CNTs.